PENGARUH MEDIA SOSIAL TERHADAP PERILAKU PEMBELIAN RAMAH LINGKUNGAN GENERASI MILENIAL DAN GENERASI Z - Ilma Wulansari Hasdiansa; Sitti Hasbiah; Nurul Fadilah Aswar (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study examines how social media affects green buying among millennials and Generation Z. This study aims to understand better how these platforms affect the attitudes and behaviours of consumers toward environmentally conscious purchasing decisions. This information can aid businesses and marketers in promoting environmentally friendly consumption and accelerating beneficial environmental changes by allowing them to target and engage with the appropriate demographic groups. This study used a descriptive research approach to examine how social media influences the environmentally conscious consumption patterns of millennials and members of Generation Z. This study carried out a quantitative examination of the questionnaire-collected data. Purposeful sampling was employed to select participants from each age group. Non-probability purposive sampling targeted specific millennial and Generation Z age groups. The sample used for this study included 300 respondents. The results of this study suggest that social media plays a significant role in influencing the preferences of members of generations millennials and z for environmentally friendly products.